AUDIENCE SERVICE PUBLIC RELATIONS METRO TV - Dewi, Yosephine Putri Sari (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2012)
The development of communication technologies has given rise to a growing public demand for the right to know and the right to information. Information has become a necessity for the community and has become an essential commodity in society. Television stations as broadcast media has a social responsibility to safeguard publicmorality as media broadcasting uses frequency broadcast into the public domain. Duties and responsibilities of broadcast media is presenting a good show broadcast program, responsibility, trustworthy, and appreciated by the public. To face competition television is rapidly increasing, the role of Public Relations is needed to build relationships with the public especially to provide services to the audience.